THE ROLE OF KATE IN GOLDSMITH'S SHE STOOPS TO CONQUER: AN ANALYTICAL APPROACH - Mariwan Hasan; Nahawand Sh. SanAhmad (Association of Social and Educational Innovation, 2020)
This research is about Kate's role in play She Stoops to Conquer, which was written by Oliver Goldsmith in 1773 in England. It is a comedy play which consists of some ethical themes. In this play, women's role and rights are focused on, in the eighteenth century in a patriarchal society and also it talks about the relation between women and their reflection in English Literature. The purpose of this research is to analyze Kate's role, whether she has a good role or not and how does she play her part. Kate generally has a good role in this play, considering all the abnormalities, eventually she could resolve, helping others, and achieves her own ambitions. Thenthe role women played in the eighteenth century will be explored. An Analytical Approach has been used to analyse the play.